Kim Nielsen. Beyond the Miracle Worker: The Remarkable Story of Anne Sullivan Macy and Her Extraordinary Friendship with Helen Keller. Boston: Beacon Press, 2009. - Georgina Kleege (Disability Studies Quarterly, 2009)
No abstract available